Numerical Simulation of Galloping Characteristics of Multi-Span Iced Eight-Bundle Conductors - Shunli, Ding; Mengqi, Cai; Bowen, Tian; Junhao, Liang; Linshu, Zhou; Chuan, Wu; Hanjie, Huang; Jun, Liu (Frontiers in Energy Research, 2022)
The numerical model of multi-span iced eight-bundle conductor is established by using the nonlinear finite element method, the galloping of the line under different parameters is simulated, and the tension in the galloping process is analyzed. Based on the aerodynamic characteristics and galloping characteristics of conductors, the galloping modes, frequency characteristics, vibration amplitudes and galloping orbits of multi-span lines under different wind velocities, span lengths, ice-shape and number of spans are analyzed, which compared with those of single-span lines. It is demonstrated that there are differences in galloping characteristics between multi-span transmission lines and single-span lines, and each span of transmission line are different, so it should be fully considered in the research of galloping prevention and control technology.